JURIDICAL ANALYSIS OF THE CASE OF THE USE OF EXPLOSIVES IN FISHING IN CANTIGI WATERS BY THE DITPOLAIRUD - Widya Puteri Cahyani; Dinda Try Ramadhanti; Dewi Rohani Sriayu Sundoro; Diky Dikrurrahman (Jurnal Abdisci, 2025)
Abstract. Background. This paper examines the juridical aspects of the use of explosives in fishing by the Ditpolairud through the perspective of the Criminal Code (KUHP) Article 1 Paragraph (1) of Emergency Law No. 12 of 1951 concerning Explosives and Firearms. Methods. This research uses Normative and Qualitative Juridical Methods supported by document analysis. The data collection technique is carried out by means of a literature study for secondary data and presented descriptively. Result. The results of this study show that fishing has been carried out using explosives without a permit which is prohibited according to the provisions of laws and regulations and has met the elements in Article 1 Paragraph (1) of Emergency Law No. 12 of 1951 concerning Explosives and Firearms, and or Article 84 Paragraph (1) of Law No. 45 of 2009 concerning Fisheries, this case occurred in the waters of the Cantigi Sea, Indramayu on Wednesday, May 19, 2021 at around 21.15 WIB. Conclusion. Therefore, the Ditpolairud conducted an investigation to find evidence and could conclude the analysis and juridical of the case.